A Neuro-Motor Training-Based Basic Movement Learning Model on Students' Neural Efficiency and Motor Performance - Muhammad Noer Fadlan; Dina Hidayati Hutasuhut (Attractive : Innovative Education Journal, 2025)
This study aims to: (1) analyze the effect of the basic motor learning model based on neuro-motor training on the neural efficiency of elementary school students, and (2) analyze its effect on the motor performance of elementary school students. The study used a quantitative approach with a quasi-experimental design (pretest–posttest control group design). The study subjects were 60 elementary school students divided into an experimental group (n = 30) and a control group (n = 30). Data were collected using neural efficiency tests and motor performance tests, then analyzed using descriptive statistics and Analysis of Covariance (ANCOVA) with pretest scores as covariates. The results showed that the neural efficiency score of the experimental group increased significantly from pretest (M = 62.40; SD = 6.85) to posttest (M = 78.65; SD = 6.12), higher than the control group (M = 6.10). The ANCOVA test showed a significant effect of the learning model on neural efficiency (F = 18.72; p < 0.001; partial η² = 0.25). In addition, the motor performance of students in the experimental group also increased significantly compared to the control group, with the effect size being in the medium to large category. The conclusion of this study shows that the basic movement learning model based on neuro-motor training is effective in improving the neural efficiency and motor performance of elementary school students, and is recommended as a physical education learning approach based on neuroscience and empirical evidence